2022
DOI: 10.1093/mnras/stac3200
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in multiplanetary extrasolar systems

Abstract: Here we present an initial look at the dynamics and stability of 178 multiplanetary systems which are already confirmed and listed in the NASA Exoplanet Archive. To distinguish between the chaotic and regular nature of a system, the value of the MEGNO indicator for each system was determined. Almost three-quarters of them could be labelled as long-term stable. Only 45 studied systems show chaotic behaviour. We consequently investigated the effects of the number of planets and their parameters on the system sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…This point is also discussed in a different approach recently by Gajdoš & Vaňko (2023), who found that several observed exoplanetary systems have relatively short Lyapunov times (calculated from the Lyapunov exponent), even down to O(10) yr. This fact implies that the Lyapunov time is not necessarily related to the Lagrange stability of the systems, in good agreement with our finding mentioned above.…”
Section: Introductionmentioning
confidence: 78%
“…This point is also discussed in a different approach recently by Gajdoš & Vaňko (2023), who found that several observed exoplanetary systems have relatively short Lyapunov times (calculated from the Lyapunov exponent), even down to O(10) yr. This fact implies that the Lyapunov time is not necessarily related to the Lagrange stability of the systems, in good agreement with our finding mentioned above.…”
Section: Introductionmentioning
confidence: 78%
“…The original resonant architecture was then broken during a later phase of dynamical instability. This scenario is supported by dynamical population studies of exoplanetary systems (Laskar & Petit 2017;Gajdoš & Vaňko 2023) revealing how 25-45% of known multiplanet systems, and the majority of high-multiplicity systems hosting four or more planets like V1298 Tau, show the signatures of chaos and instability in their architectures. We investigate the plausible causes of the instability in Sects.…”
Section: Dynamical Excitation Of V1298 Tau B and Ementioning
confidence: 89%